Pelatihan Manajemen dan Motivasi Bagi Aparatur Desa Talang Sungai Limau Kec. Rakit Kulim Kabupaten Indragiri Hulu - Iskandar Iskandar; Hendrayani Hendrayani; Yusriadi Yusriadi; Yogie Rahmat; Hasanul Bishri; Eka Putra; T. Reza Kurniawan (Jurnal Pengabdian Kepada Masyarakat Digital, 2023)
This article was created as one of the results of Community Service activities in the assisted village of STIE Riau as a partner, namely Talang Sungai Limau Village, Rakit Kulim District, Indragiri Hulu Regency, Riau Province, which is a settlement of the Talang Mamak tribe, one of the indigenous people of Riau. Held on 24 - 25 September 2022 after a series of preparatory activities. This activity aims to increase the management capacity and motivation of village officials including village office staff, hamlet heads, RT and PKK women. Activities carried out in the form of lectures, discussions and games. From the discussions that developed with the training participants, it was revealed that village officials received little attention from universities or community social organizations around the district, let alone the province. villages and residents in general can be carried out in a sustainable manner, and are able to provide solutions for regional development both in terms of the quality of human resources and as mediators to establish cooperation or get attention from government agencies and other private institutions. Keywords: Community Service, Management Training, Motivation, Village Apparatus, Talang mamak